2016
DOI: 10.3389/fpls.2016.01301
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Characterization and Expression Analysis of the TCP Gene Family in Prunus mume

Abstract: TCP proteins, belonging to a plant-specific transcription factors family, are known to have great functions in plant development, especially flower and leaf development. However, there is little information about this gene family in Prunus mume, which is widely cultivated in China as an ornamental and fruit tree. Here a genome-wide analysis of TCP genes was performed to explore their evolution in P. mume. Nineteen PmTCPs were identified and three of them contained putative miR319 target sites. Phylogenetic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 46 publications
(76 reference statements)
1
36
0
Order By: Relevance
“…Hence, the detailed biological functions of TCP transcription factors in grapevine bud break would be an issue worthy of further investigation. the two groups was also consistent with that in other species (Xu et al, 2014;Zhou et al, 2016). Most members, such as VvTCP2, VvTCP5, VvTCP6, VvTCP7 and VvTCP14, had higher expression in young leaves (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Hence, the detailed biological functions of TCP transcription factors in grapevine bud break would be an issue worthy of further investigation. the two groups was also consistent with that in other species (Xu et al, 2014;Zhou et al, 2016). Most members, such as VvTCP2, VvTCP5, VvTCP6, VvTCP7 and VvTCP14, had higher expression in young leaves (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Family members of TCP genes in Arabidopsis (Arabidopsis thaliana) (Yao et al, 2007), rice (Oryza sativa) (Yao et al, 2007), cotton (Gossypium arboretum and Gossypium raimondii) (Ma et al, 2014(Ma et al, , 2016, apple (Malus domestica) (Xu et al, 2014), tomato (Solanum lycopersicum) (Parapunova et al, 2014), watermelon (Citrullus lanatus) (Shi et al, 2016) and Prunus mume (Zhou et al, 2016) have been identified, and some of the genes have been well characterised, while no comprehensive analysis of grapevine has been reported until now. In our study, 15 TCP members in the grapevine genome were identified.…”
Section: Discussionmentioning
confidence: 99%
“…The sequences of TCP family members in C. lanatus, O. sativa, Brassica rapa for constructing phylogenetic tree were obtained from PlantTFDB TF database (http://planttfdb.cbi.pku.edu.cn/, v3.0). The number of TCP family genes were obtained in Arabidopsis thaliana (Wei et al, 2016), O. sativa (Yao et al, 2007), L. esculentum (Parapunova et al, 2014), P. mume (Zhou et al, 2016), C. lanatus (Shi et al, 2016), turnip (Du et al, 2017), Chinese cabbage (Liu et al, 2018), and Gossypium raimondii (Ma et al, 2014).…”
Section: Mining Of Grape Tcp Gene Familymentioning
confidence: 99%
“…Recently, TCP gene family has been reported in various plants, for instance, 24 TCP genes in Arabidopsis,30 in Lycopersicon esculentum,28 in Oryza sativa,33 in Populus euphratica,36 in Populus trichocarpa,27 in Citrullus lanatus,19 in Prunus mume (Martin-Trillo and Cubas, 2010;Parapunova et al, 2014;Ma et al, 2016;Shi et al, 2016;Zhou et al, 2016). The grape is an ideal model for understanding the berry development in perennial fruit species.…”
Section: Introductionmentioning
confidence: 99%
“…Both CYC and DICH genes belong to the TCP gene family (abbreviation for TEOSINTE BRANCHED 1 [ TB1 ] from Zea mays , CYCLOIDEA [ CYC ] from Antirrhinum majus and PROLIFERATION CELL FACTOR 1 and 2 [ PCF1 and PCF2 ] from Oryza sativa ) and have been comprehensively studied in model and non‐model species (Boyden et al., ; Broholm, ; Damerval and Manuel, ; De Paolo et al., ; Fambrini and Pugliesi, ; Galego and Almeida, ; Hileman et al., ; Howarth and Donoghue, , ; Lei et al., ; Li et al., ; Lin et al., ; Luo et al., ; Madrigal et al., ; Reardon et al., ; Su et al., ; Wei et al., ; Zhong and Kellogg, ; Zhou et al., ). On the other hand, RAD and DIV belong to the MYB ( Myeloblastosis ) gene superfamily and have been less studied in comparison to the TCP genes (Corley et al., ; Costa et al., ; Galego and Almeida, ; Luo et al., ; MacHemer et al., ; Reardon et al., ; Su et al., ; Valoroso et al., ).…”
mentioning
confidence: 99%